Chemical analyses of the earliest pigment residues from the uttermost part of the planet (Beagle Channel region, Tierra del Fuego, Southern South America) - Fiore, Danae (2008)
This paper presents the results of chemical analyses of the organic and inorganic fractions of pigment residues found in three archaeological sites located in the Beagle Channel region, Tierra del Fuego, Southern South America. Twenty-one archaeological samples have been analysed through XRD, SEM-EDX, FT-IR and GC-MS in order to characterise their inorganic colouring components and to search for the presence of organic substances used as binders. Lipids found in some samples are considered as potential binders. These organic components are compared to those found in archaeological sediment samples from the same layers where the pigments have been found, in order to search for potential taphonomic contaminations of the latter by the former. Results show that such contaminations are unlikely, hence the lipid contents are deemed of anthropic origin. The pigment sample results are also compared to data from analyses of natural sediment samples collected in several localities of the Beagle Channel in order to search for potential natural pigment sources. Results show that organic and inorganic components of these sediments are not the same than those present in the archaeological pigment samples, hence the pigment raw material sources have not been yet located. All these data provide for the first time evidence of the existence of ancient activities of pigment sourcing and paint preparation with organic binders which range from 6000 BP to 1900 BP in the southernmost region of the planet.